Computers in English Class, Circa 1974. - Howard, Jennifer (Humanities)
The article focuses on the use of computers in teaching English and American poetry to college students with information on the digital humanities project conducted by professors Robert Scholes and Andries "Andy" van Dam under the grants from the Office of Digital Humanities of the National Endowment for the Humanities (NEH) entitled "An Experiment in Computer-Based Education Using Hypertext." The advantages and benefits of the approach to poetry courses since 1974 are also mentioned.